Guidance on C-reactive protein point-of-care testing and complementary strategies to improve antibiotic prescribing for adults with lower respiratory tract infections in primary care - Van Hecke, Oliver; Bjerrum, Lars; Gentile, Ivan; Hopstaken, Rogier; Melbye, Hasse; Plate, Andreas; Verbakel, Jan Y.; Llor, Carl; Staiano, Annamaria (Frontiers in Medicine, 2023)
The world faces the threat of increasing antimicrobial resistance, and there is growing consensus that swift action must be taken to improve the rational use of antibiotics and increase the stewardship of antibiotics to safeguard this key resource in modern healthcare. This paper provides the perspective of an international group of experts on the role of C-reactive protein point-of-care testing (CRP POCT) and other complementary strategies to improve antibiotic stewardship in primary care, with regards to the diagnosis and treatment of adult patients presenting symptoms of lower respiratory tract infections (LRTIs). It provides guidance regarding the clinical assessment of symptoms in combination with C-reactive protein (CRP) results, at the point of care, to support the management decision, and discusses enhanced patient communication and delayed prescribing as complementary strategies to decrease the inappropriate use of antibiotics. Recommendation: CRP POCT should be promoted to improve the identification of adults presenting with symptoms of LRTIs in primary care who might gain additional benefit from antibiotic treatment. Appropriateness of antibiotic use can be maximized when CRP POCT is used together with complementary strategies such as enhanced communication skills training and delayed prescribing in addition to routine safety netting.